2020
DOI: 10.3390/nu12020422
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effects of Calorie Restriction (CR) and CR Mimetics Based on the Senoinflammation Concept

Abstract: Chronic inflammation, a pervasive feature of the aging process, is defined by a continuous, multifarious, low-grade inflammatory response. It is a sustained and systemic phenomenon that aggravates aging and can lead to age-related chronic diseases. In recent years, our understanding of age-related chronic inflammation has advanced through a large number of investigations on aging and calorie restriction (CR). A broader view of age-related inflammation is the concept of senoinflammation, which has an outlook be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 262 publications
(300 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, we found that both long-term (8 months) rapamycin and acarbose treatments were associated with a comparable, broad reduction in RE transcripts (Fig. 1B), consistent with the notion that these compounds are 'calorie restriction mimetics' and may act via similar pathways (17). This effect was particularly clear when we examined RE/TE reductions by major sub-type (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, we found that both long-term (8 months) rapamycin and acarbose treatments were associated with a comparable, broad reduction in RE transcripts (Fig. 1B), consistent with the notion that these compounds are 'calorie restriction mimetics' and may act via similar pathways (17). This effect was particularly clear when we examined RE/TE reductions by major sub-type (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Calorie restriction is one of the most promising approaches for reducing the negative effects of metabolic disorders, age-related diseases, and pathologies associated with metaflammation ( Park et al, 2012 ; Ma et al, 2020 ). In animal studies, it has been shown that reducing calorie intake increases life span and helps to lower blood glucose and insulin levels ( Redman and Ravussin, 2011 ; Kim et al, 2020 ). There is currently evidence that CR for 2 years by 15% in healthy, non-obese people leads to a decrease in systemic oxidative damage ( Redman et al, 2018 ).…”
Section: Metaflammation and Metaflammasomementioning
confidence: 99%
“…Chronic, sterile, low-level inflammation has been considered as a factor that accelerates the aging process, which is referred to as “inflammaging” [ 9 , 17 ] or “senoinflammation” [ 15 ]. This persistent low-level inflammation conferring toxic insults on tissues not only accelerates aging but also causes aging-related diseases.…”
Section: Chronic Low-level Inflammation and Agingmentioning
confidence: 99%
“…CR is reported to effectively reduce circulating inflammatory signatures that are induced by aging or obesity [ 55 , 56 , 57 ]. The molecular mechanisms by which CR affects aging and related diseases are well reviewed elsewhere under the concept of “senoinflammation” [ 15 ]. Several studies have already indicated the inhibitory effect of CR on the aging-related increase of inflammation.…”
Section: Modulation Of Inflammaging By Calorie Restriction (Cr) VImentioning
confidence: 99%
See 1 more Smart Citation